2012
DOI: 10.1068/p7031
|View full text |Cite
|
Sign up to set email alerts
|

With or without a Hole: Young Infants' Sensitivity for Topological versus Geometric Property

Abstract: Evidence from adult psychophysics, brain imaging, and honeybee's behaviour has been reported to support the notion that topological properties are the primitives of visual representation (Chen, 1982 Science 218 699-700). Here, we ask how the sensitivity to topological property might originate during development. Specifically, we tested 1.5- to 6-month-old infants' visual sensitivity for topological versus geometric properties with the forced-choice novelty preference technique. A disk and a ring were used in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
(30 reference statements)
2
19
0
Order By: Relevance
“…A topological theory, which holds that the extraction of TP serves as the starting point of object perception, has been proposed to address the fundamental question of what are the primitives of visual perception (Chen, 2005, 1982). This theory has been supported by sufficient evidence across species from insects, rodents to humans, demonstrating that visual system is more sensitive to detect TP differences in images than other non-TP shape differences, and TP is processed automatically and with higher priority (Chen, 1982; Chen et al, 2003; Chien et al, 2012; Han et al, 1999; Huang et al, 2019, 2018, 2011; Todd et al, 1998). Previous evidence from human brain imaging, i.e., functional magnetic resonance imaging (fMRI), however, shows that the inferior temporal cortex (IT) was involved in TP processing (Wang et al, 2007; Zhou et al, 2010; Zhuo et al, 2003).…”
Section: Introductionmentioning
confidence: 91%
“…A topological theory, which holds that the extraction of TP serves as the starting point of object perception, has been proposed to address the fundamental question of what are the primitives of visual perception (Chen, 2005, 1982). This theory has been supported by sufficient evidence across species from insects, rodents to humans, demonstrating that visual system is more sensitive to detect TP differences in images than other non-TP shape differences, and TP is processed automatically and with higher priority (Chen, 1982; Chen et al, 2003; Chien et al, 2012; Han et al, 1999; Huang et al, 2019, 2018, 2011; Todd et al, 1998). Previous evidence from human brain imaging, i.e., functional magnetic resonance imaging (fMRI), however, shows that the inferior temporal cortex (IT) was involved in TP processing (Wang et al, 2007; Zhou et al, 2010; Zhuo et al, 2003).…”
Section: Introductionmentioning
confidence: 91%
“…Indeed, infants' sensitivity to topology appears to precede their sensitivity to geometric properties such as shape. In a recent study, Chien et al (2012) found that infants at 1.5 months could discriminate objects by topology, but it was not until 3.5 months that they could discriminate objects by shape. Similar results on the primacy of topological class over shape information have been found in adults (L. Chen, 1982) and even in bees (L. Chen, Zhang, & Srinivasan, 2003).…”
Section: Introductionmentioning
confidence: 95%
“…We reasoned that the topological distinction between these objects would be readily detectable by infants, since much younger infants have been shown to discriminate disks and rings in twodimensional displays (e.g. Chien, et al 2012) and to use topological class to reason about how three-dimensional objects should interact (e.g. Hespos & Baillargeon, 2001a;Wang, et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, in other tasks, including multiple-object tracking (Zhou et al, 2010 ) and long-range apparent motion perception (Zhuo et al, 2003 ), Chen et al further confirmed that the human visual perception is indeed sensitive to the connectivity or the hole of stimuli. The studies on infants also support the precedence of topological perception (Piaget and Inhelder, 1956 ; Darke, 1982 ; Chien et al, 2012 ; Kibbe and Leslie, 2016 ). It was found that newborns, even as young as few days old, display the preference of using the topological information to discriminate objects (Turati et al, 2003 ).…”
Section: Introductionmentioning
confidence: 53%